Identification of genome-wide nucleotide sites associated with mammalian virulence in influenza A viruses - Yousong Peng; Wenfei Zhu; Zhaomin Feng; Zhaozhong Zhu; Zheng Zhang; Yongkun Chen; Suli Liu; Aiping Wu; Dayan Wang; Yuelong Shu; Taijiao Jiang (Elsevier, 2020)
The virulence of influenza viruses is a complex multigenic trait. Previous studies about the virulence determinants of influenza viruses mainly focused on amino acid sites, ignoring the influence of nucleotide mutations. In this study, we collected >200 viral strains from 21 subtypes of influenza A viruses with virulence in mammals and obtained over 100 mammalian virulence-related nucleotide sites across the genome by computational analysis. Fifty of these nucleotide sites only experienced synonymous mutations. Experiments showed that synonymous mutations in three high-scoring nucleotide sites, i.e., PB1-2031, PB1-633, and PB1-720, enhanced the pathogenicity of the influenza A(H1N1) viruses in mice. Besides, machine-learning models with accepted accuracy for predicting mammalian virulence of influenza A viruses were built. Overall, this study highlighted the importance of nucleotide mutations, especially synonymous mutations in viral virulence, and provided rapid methods for evaluating the virulence of influenza A viruses. It could be helpful for early warning of newly emerging influenza A viruses.